Patterns of expression of VEGFR2, PDGFRs and c-Kit in pediatric patients with high grade non-rhabdomyosarcoma soft tissue sarcoma - Elnadi, Enas M.; Salama, Asmaa I.; Abd Elaziz, Abd Elaziz Saad; Ahmed, Gehad T.; ELwakeel, Madeeha A.; Kamal, Mohamed K.; Kieran, Mark W.; Elhaddad, Alaa M. (Frontiers in Oncology, 2024)
IntroductionActivated vascular endothelial growth factor receptors (VEGFRs), platelet-derived growth factor receptors (PDGFRs) and c-Kit have been shown to be involved in the growth, invasion and metastasis of non-rhabdomyosarcoma soft tissue sarcoma tumor (NRSTS) with promising results for targeted therapy. Our aim was to assess the expression of these markers among different histological types and correlate with outcomes.Material and methodsThis retrospective study included pediatric patients aged ≤ 18 years diagnosed with high-grade NRSTS who were treated at Children Cancer Hospital Egypt 57357 as per the COG NRSTS protocol (ARST0332). Expression of VEGFR2, PDGFRs (α and β) and c-Kit in tumor tissue was assessed by immunohistochemistry and correlated with clinical outcome.ResultsOf 113 patients, 96 were eligible for the analysis with a median age of 11 years. Overall, 32.3% demonstrated high expression of PDGFRα, 17.7% for PDGFRβ, 19.8% for VEGFR2 and 8.3% exhibited positive expression for c-kit on the tumor cells. Most cases of synovial sarcoma (45.8%) and 43.7% of patients with undifferentiated sarcoma exhibited high expression of PDGFRα while 41.6% of MPNST showed high expression to PDGFRβ. The 5-year overall survival (OS), event free survival and relapse free survival (RFS) for the whole cohort were 59%, 54% and 60% respectively. In univariate analyses, only PDGFRα had a negative prognostic impact on relapse free survival (RFS) (p=0.03). In multivariate analyses, VEGFR2 was found to have a negative prognostic impact for OS (p = 0.02).ConclusionOur findings indicated that tyrosine kinase receptors are upregulated in NRSTS and exhibited a distinct expression pattern within various subgroups. High expression of VEGFR2 and PDGFRα significantly correlated with reduced survival and may guide targeted therapy approaches for this poor prognosis group of patients.